Underserved groups in dysphagia intervention trials in Parkinson¿s disease: A scoping review - Hirschwald, Julia Antonia; Walshe, Margaret (My University, 2024)
Background: Underserved groups in Parkinson's disease (PD) intervention studies are well recognised. However, it remains unclear whether these exclusions apply to oropharyngeal dysphagia (OD) intervention studies in PD. The aim of this scoping review was to identify characteristics of included participants and underserved groups in intervention studies in OD in PD. Methods: Six electronic databases and one trial registry were searched without language restrictions. Screening of studies and data extraction were independently conducted by four reviewers. Results: Of the 26 studies included, none fully reported the participants' ethnicity. Where data was available, 70% of participants were male with a mean age of 68 years, mean PD duration of 7.26 years, median Hoehn and Yahr stage of 2.5, mild OD and mostly recruited from movement disorders clinics. Underserved groups were younger people (< 50 years), older people (≥ 80 years), women, non-white people, people with severe OD and PD, longer PD duration, other neurological conditions, cognitive impairment/dementia, and depression. Conclusions: Careful consideration of all characteristics of individuals with OD in PD is essential for improving the external validity of studies. This will enhance the generalisability of research findings to the broader PD population, ultimately strengthening the evidence base for OD interventions in PD.
PUBLISHED
Keywords: Dysphagia; Exclusion; Intervention trial; Parkinson’s disease; Underserved group; Ageing; Inclusive Society; CLINICAL TRIAL; Age-related disability; Chronic Health Condition; Communication; Health; Social exclusion